Complementary Pathways to Protection: Promoting the Integration and Inclusion of Refugees in Europe?. Issue 1 (July 2020) - van Selm, Joanne
Traditional solutions for refugee protection and integration—repatriation, local integration, and resettlement—have become difficult, and countries in Europe are exploring other means of providing protection through what are known as complementary pathways . Complementary pathways are relatively small in scope and cover a range of programs and refugee populations. Broadly speaking, they include humanitarian admission programs, community or private sponsorship, some labor mobility and student scholarship programs, (extended) family admissions, and humanitarian visas that allow legal arrival for asylum seekers. I trace the development of these pathways and how they have emerged in different countries; I also consider key questions that they raise about refugee integration and the future of refugee protection.